(untitled) (Sociologisk Forskning, 2011)
Time as a welfare factor This article presents the results of an archive study of working time development in Sweden. It investigates how structural policy change is moving from a social discourse closely related to Swedish welfare reforms, towards an economic discourse motivated by financial arguments. By doing so, the political measures to solve working time related problems in today’s flexible working life appear to be contradictory. On one side we find time-poor people on the labour market mainly supported by tax-reductions and private time saving solutions. On the other side we find time-rich people mainly supported by activation programs and/or welfare benefits. This is a system and a policy strategy that obviously disregards the other side of the coin.